Pilocytic Astrocytoma of the Cerebellopontine Angle with cerebrospinal fluid Spread in an Adult: A Case Report - KURŞUN, MELTEM; OĞUZSOY, TUBA; BOZKURT, SÜHEYLA; BAYRAKLI, FATİH; BIYIKLI, ERHAN (My University, 2022)
Introduction Pilocytic astrocytoma of the cerebellopontine angle (CPA) is uncommon, and its spread to the cerebrospinal fluid (CSF) at the time of diagnosis has not been reported in the literature. Case Presentation We report the case of a 33-year-old man with multifocal pilocytic astrocytoma diagnosed by magnetic resonance imaging (MRI) and confirmed by histopathological examination, and present the radiological and histopathological findings. Conclusion In the case herein reported, we observed spread of the pilocytic astrocytoma of the CPA to the CSF at the initial diagnosis, and early detection by MRI is very important regarding the treatment modality and prognosis.

Introdução O astrocitoma pilocítico no ângulo pontocerebelar (APC) é incomum, e sua disseminação liquórica no momento do diagnóstico não foi relatada na literatura. Apresentação do Caso Relatamos o caso de um homem de 33 anos com astrocitoma pilocítico multifocal diagnosticado por ressonância magnética (RM) e confirmado por exame histopatológico, e apresentamos os achados radiológicos e histopatológicos. Conclusão No caso relatado, observou-se disseminação liquórica de astrocitoma pilocítico no APC no diagnóstico inicial, e a detecção precoce por RM é muito importante para a modalidade de tratamento e o prognóstico.
Astrocitoma pilocítico no ângulo pontocerebelar com disseminação liquórica em paciente adulto: Relato de caso
Keywords: Tıp; Dahili Tıp Bilimleri; Radyodiagnostik; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Radiodiagnostic; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji ve Ultrason Teknolojisi; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Radyoloji, Nükleer Tıp ve Görüntüleme; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Radiological and Ultrasound Technology; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Radiology, Nuclear Medicine and Imaging; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; ângulo pontocerebelar; astrocitoma pilocítico; schwannoma vestibular; cerebellopontine angle; pilocytic astrocytoma; vestibular schwannoma